Partial Recall - Benally, Suzanne (New Press, 1992)
In Partial Recall, twelve Native American artists and writers look deep into the images that have shaped our ideas of "Indianness," and explore the complex relationship of photography to identity. For this volume, edited and introduced by Lucy Lippard, each contributor has chosen one or two photographs as the point of departure for their original poetic, historical, political, or autobiographical essays. With an additional portfolio of more than sixty photographs drawn from around the country, Partial Recall is a unique and valuable anthology.
OCLC: 26767689
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Manifest Manners: Narratives on Postindian Survivance - Vizenor, Gerald Robert (Univ. of Nebraska Press, 2010)
Combines post-modern theory with the comic wisdom of the tribal trickster to explore the effects of nostalgic simulations of "Indian-ness".
OCLC: 837681052
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé